2006
DOI: 10.1007/s11136-006-0016-x
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Functional Status and Depressive Symptoms with Health-related Quality of Life in Cancer Patients

Abstract: Associations of functional status (as measured with the Karnofsky Index), depressive symptoms (as assessed with the Beck Depression Inventory), and sociodemographic characteristics with health-related quality of life (HrQoL; measured with the EORTC Quality of Life Questionnaire QLQ-C30) were assessed in 170 recently diagnosed cancer patients. A better functional status (p<0.001) and a lower level of depressive symptoms (p<0.001) were associated with better HrQoL. In addition, an interaction effect of functiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
15
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 17 publications
3
15
0
Order By: Relevance
“…Depression tended to have somewhat stronger effects than pain, and depression-pain comorbidity yielded the greatest impairment. The relationship between symptom burden and quality of life in cancer patients has been noted,6 as has the particularly strong effects of depression 63,64. The frequent co-occurrence of pain-depression (45% in our sample) and their additive adverse effects make them an especially pernicious symptom dyad 21.…”
Section: Discussionmentioning
confidence: 59%
“…Depression tended to have somewhat stronger effects than pain, and depression-pain comorbidity yielded the greatest impairment. The relationship between symptom burden and quality of life in cancer patients has been noted,6 as has the particularly strong effects of depression 63,64. The frequent co-occurrence of pain-depression (45% in our sample) and their additive adverse effects make them an especially pernicious symptom dyad 21.…”
Section: Discussionmentioning
confidence: 59%
“…In cancer patients, both functional status and depression affected HRQoL [17]. However, an interaction effect was also found: In patients with low functional status, as compared to those with high functional status, depression had no additional impact on HRQoL.…”
Section: Discussionmentioning
confidence: 88%
“…Pinquart et al reported that a lower level of depressive symptoms was associated with better quality of life in cancer patients [21]. Frick et al reported that anxiety and depression were significantly correlated with impaired quality of life [4].…”
Section: Discussionmentioning
confidence: 99%